2009
DOI: 10.1016/j.cell.2009.03.047
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: A Pleiotropically Acting MicroRNA, miR-31, Inhibits Breast Cancer Metastasis

Abstract: SUMMARY MicroRNAs are well-suited to regulate tumor metastasis due to their capacity to coordinately repress numerous target genes, thereby potentially enabling their intervention at multiple steps of the invasion-metastasis cascade. We identify a microRNA exemplifying these attributes, miR-31, whose expression correlates inversely with metastasis in human breast cancer patients. Overexpression of miR-31 in otherwise-aggressive breast tumor cells suppresses metastasis. We deploy a stable microRNA sponge strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

32
687
8
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 778 publications
(732 citation statements)
references
References 40 publications
32
687
8
5
Order By: Relevance
“…Enforced expression of miR-409 could suppress the migration, invasion and metastasis of GC cells in vitro and in vivo. We further identified RDX, a putative pro-metastatic gene, 20,25 as a direct functional target of miR-409. To our knowledge, this is the first study to explore the role of miR-409 in cancer, and our results indicate that miR-409 acts to suppress metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enforced expression of miR-409 could suppress the migration, invasion and metastasis of GC cells in vitro and in vivo. We further identified RDX, a putative pro-metastatic gene, 20,25 as a direct functional target of miR-409. To our knowledge, this is the first study to explore the role of miR-409 in cancer, and our results indicate that miR-409 acts to suppress metastasis in GC.…”
Section: Discussionmentioning
confidence: 99%
“…21 RDX was originally identified as a constituent of adherence junctions in the livers of rats, 36 and it has more recently been implicated in cancer progression and metastasis. 20,24,25,39 It has been reported that RDX may cooperate with ITGA5 and RhoA to affect three distinct steps in the invasionmetastasis cascade in vivo, local invasion, early post-intravasation events and metastatic colonisation. 25 Silencing of RDX has also been found to suppress the migration and invasion of GC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 miR-31 uses multiple mechanisms to oppose the breast cancer metastasis. 18 miR-208 regulates cardiac growth and gene expression in response to stress and hormonal signaling. 14 Autophagy is regulated by a variety of factors in which the autophagy-related genes (ATGs) control the different stages of autophagy including initiation and elongation.…”
mentioning
confidence: 99%
“…The miRNAs act as either oncogenes [13][14][15] or tumour suppressors. [16][17][18] The miRNA let-7a has been characterised as a tumour suppressor in several human cancers. [19][20][21][22][23][24] Dong et al 25 reported that let-7a is downregulated in resected prostate cancer samples and in prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%